2017
DOI: 10.1186/s13068-017-0751-y
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic engineering of Saccharomyces cerevisiae to produce a reduced viscosity oil from lignocellulose

Abstract: BackgroundAcetyl-triacylglycerols (acetyl-TAGs) are unusual triacylglycerol (TAG) molecules that contain an sn-3 acetate group. Compared to typical triacylglycerol molecules (here referred to as long chain TAGs; lcTAGs), acetyl-TAGs possess reduced viscosity and improved cold temperature properties, which may allow direct use as a drop-in diesel fuel. Their different chemical and physical properties also make acetyl-TAGs useful for other applications such as lubricants and plasticizers. Acetyl-TAGs can be synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 44 publications
2
11
0
Order By: Relevance
“…However, lipid accumulation was not significantly increased by the insertion of DAcT activity in Y. lipolytica . Similar results have been reported by Tran, Breuer, et al (), who transformed S. cerevisiae H1246 using EaDAcT isolated from Euonymus alatus . It was previously observed that the insertion of native DGA1 or DGA2 acyltransferase genes (Gajdoš, Ledesma‐Amaro, Nicaud, Čertík, & Rossignol, ) and DGAT2 gene from mouse (Ledesma‐Amaro, unpublished data) into the Q4 mutant of Y. lipolytica under the control of a strong promoter was able to trigger lipid accumulation at an even higher rate than the wild type.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, lipid accumulation was not significantly increased by the insertion of DAcT activity in Y. lipolytica . Similar results have been reported by Tran, Breuer, et al (), who transformed S. cerevisiae H1246 using EaDAcT isolated from Euonymus alatus . It was previously observed that the insertion of native DGA1 or DGA2 acyltransferase genes (Gajdoš, Ledesma‐Amaro, Nicaud, Čertík, & Rossignol, ) and DGAT2 gene from mouse (Ledesma‐Amaro, unpublished data) into the Q4 mutant of Y. lipolytica under the control of a strong promoter was able to trigger lipid accumulation at an even higher rate than the wild type.…”
Section: Discussionsupporting
confidence: 90%
“…However, lipid accumulation was not significantly increased by the insertion of DAcT activity in Y. lipolytica. Similar results have been reported by Tran, Breuer, et al (2017), who transformed S. cerevisiae H1246 using…”
Section: Discussionsupporting
confidence: 90%
“…In a recent study, Tran et al aimed to produce acetyl-triacylglycerols, which possess reduced viscosity and improved cold temperature properties over typical long-chain triacylglycerol molecules (lcTAGs). [76] A diacylglycerol acetyltransferase from Euonymus alatus (EaDAcT) was expressed in S. cerevisiae strains engineered to ferment xylose, enabling acetyl-TAGs accumulation using xylose as a carbon source. The deletion of four genes coding for enzymes involved in lcTAG production improved the proportion of acetyl-TAGs within total lipids.…”
Section: Acetyl-coa-derived Metabolitesmentioning
confidence: 99%
“…Interestingly, xylose cultivation was found to increase the accumulation of lcTAGs but decreased the production of acetyl‐TAGs compared to glucose cultivation, indicating different metabolic patterns of the two sugars in lipids biosynthesis. [ 76 ]…”
Section: Leveraging Xylose Metabolism To Produce Non‐ethanol Bioproductsmentioning
confidence: 99%
“…To solve this problem, strain engineering has generated industrial fungal strains that have superior performance compared to wild type strains. Genetic engineering approaches have been developed for industrially used fungal species and strains in order to increase their enzyme production (Ha et al, 2011;Tran et al, 2017). However, most of these methods are available for only a limited number of model or industrial fungi.…”
Section: Accepted Manuscriptmentioning
confidence: 99%